Planning Atlas Uttar Pradesh 2006 - Planning Commission (Planning Commission, 2006)
Inter-regional disparities are persisting as a problem in the development of Uttar Pradesh. Even after continuous efforts by Government, these problems could not be eradicated. In this context, the Planning Department has been preparing indicators of development since last many years to find out the quantitative estimates for district/regional level of development. These indicators also point out as to what extent inter-di strict, inter-regional and inter state disparities exist. They provide better understanding of issues involved and accordingly indicate the priority areas for reducing regional imbalances.
Area Planning Division, State Planning Institute, Planning Department, Government of Uttar Pradesh
Area Planning Division, State Planning Institute, Planning Department, Government of Uttar Pradesh